LINGUOCULTUROLOGICAL STUDY OF THE LANGUAGE OF ADVERTISING (on the material of English and Karakalpak languages) - Кулдашев А., Торежанова Алтынай (Galaxy International Interdisciplinary Research Journal, 2023)
This article is devoted to the study of advertising discourse in the American version of the English language. Advertising is a mirror of the culture of the country, its mentality and national character, which reflects all socio-cultural phenomena. The study reveals not only the linguistic and cultural features of advertising slogans, but also conducts their linguostylistic analysis in order to identify the cultural characteristics of American society.